2017
DOI: 10.3390/ijerph14020130
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impacts of Anthropogenic Disturbance on Seawater and Sediment Microbial Communities in Korean Coastal Waters Using Metagenomics Analysis

Abstract: The coastal ecosystems are considered as one of the most dynamic and vulnerable environments under various anthropogenic developments and the effects of climate change. Variations in the composition and diversity of microbial communities may be a good indicator for determining whether the marine ecosystems are affected by complex forcing stressors. DNA sequence-based metagenomics has recently emerged as a promising tool for analyzing the structure and diversity of microbial communities based on environmental D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…Microbial communities in the sediments had higher diversity than in the water samples. This conclusion is reasonable as has been established through numerous studies of various aquatic ecosystems (Feng et al, 2009;Shulse et al, 2017;Sogin et al, 2006;Won et al, 2017). Higher microbial diversity in marine sediments is thought to be because sediments offer the surface for interaction of water column-derived organic matter with benthic microbial communities (Probandt et al, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…Microbial communities in the sediments had higher diversity than in the water samples. This conclusion is reasonable as has been established through numerous studies of various aquatic ecosystems (Feng et al, 2009;Shulse et al, 2017;Sogin et al, 2006;Won et al, 2017). Higher microbial diversity in marine sediments is thought to be because sediments offer the surface for interaction of water column-derived organic matter with benthic microbial communities (Probandt et al, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…Marine environments represent the richest source of new genes, enzymes, and natural products [5]. Marine bacterial community structure is affected by several factors such as inorganic nutrient concentration [6], N [7,8], P [7], change in season, adjacent habitat [9], depth [8,10], oxygen [10], protist predation pressure [11], salinity [7,8,12], dominance of algae, particulate organic carbon, Si (OH) 4 [8], human disturbance, and sand mining activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…The contemporary advances in NGS have not only enabled finer characterization of bacterial genomes but also provided deeper taxonomic identification of complex microbiomes [15]. NGS approach was employed to survey microbial communities from several marine environments such as the Gulf of Mexico [16,17], the Georgetown Coast, Malaysia [18], Malipo Beach, South Korea [19], the Canadian Arctic archipelago [8], and the South Sea, Korea [13].…”
Section: Introductionmentioning
confidence: 99%
“…The Proteobacteria, especially DeltaProteobacteria and GammaProteobacteria, were found to be the most abundant in all three sediments. Won et al (2017) also showed that the Delta-and GammaProteobacteria were dominant in the sediment and deep sea samples from Korea. Two abundant orders of Deproteobacteria, Desulfobacterales in the Ongnyeon region and Desulfuromonadales in Yeongjong Island, include sulfate-reducing bacteria and sulfur-oxidizing bacteria, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…In particular, due to intensive human activities, such as sewage discharge, excessive fertilizer use, land reclamation projects, and concentration of human civilization near coastal regions, coastal areas face serious ecosystem pollution which is reflected by over-nutrition and lower amounts of dissolved oxygen (Lee et al, 2011;Waycott et al, 2009). Tidal flats in the west coast wetlands of the Korean peninsula are known to be the fifth largest in the world, after the north coast of Europe, the wetlands of the Amazon, the east coast of Canada, and the eastern wetlands of America (Cho et al, 2004;Wilms et al, 2006;Won et al, 2017). The tidal flats of Incheon in Korea are known for their variety of geographical types.…”
Section: Introductionmentioning
confidence: 99%